The Effects of a Forest Therapy on Work-Related Stress for Employees in the Manufacturing Industry: Randomized Control Study - Han Choi; Yo-Han Jeon; Jin-Woo Han; Joo Moon; Soo-Yeon Kim; Jong-Min Woo (SAGE Publishing, 2022)
Background The effect of a forest therapy in a natural environment noted that the forest therapy induced a state of relaxation among workers, thereby decreasing cortisol levels and work-related stress. Objective The primary objective of this study is to determine the effects of the forest therapy for employees in the manufacturing industry on psychological stress responds, stress hormone and heart rate variability (HRV). The secondary objective is to determine the effects of the forest therapy for employees in the manufacturing industry on cytotoxic activity of natural killer (NK) cells, health-related quality of life and mood states compare to urban untreated and remained in urban environment. Methods Forty-two employees were recruited from a single workplace located in Incheon city, Republic of Korea. Participants were allocated to either an experimental group (n= 21), wherein they participated in the forest therapy and or a control group (n= 21), wherein they were given no treatment. Participants were assigned to these groups on a randomized, open-label basis. Pre and post-test measures of natural killer (NK) cell activity, salivary cortisol, heart rate variability (HRV), health-related quality of life, stress response, and mood states were taken for both groups. Results The results showed that participants who took part in the forest therapy showed greater physiological improvement when compared to those in the control group, as indicated by a significant increase in some HRV measures. The forest therapy also contributed to a significantly greater decrease in work-related stress symptoms and a significantly greater improvement in health-related quality of life and mood states compared to participants in the control group. Conclusions These results may suggest that the forest therapy could be an effective means of relaxation technique, reducing stress and leads to an increase in positive mood for employees in the manufacturing industry.